Vivian Maier street photographer - Maier, Vivian 1926-2009; Maloof, John (PowerHouse Books, 2011)
"A good street photographer must be possessed of many talents: an eye for detail, light, and composition; impeccable timing; a populist or humanitarian outlook; and a tireless ability to constantly shoot, shoot, shoot, shoot and never miss a moment. It is hard enough to find these qualities in trained photographers with the benefit of schooling and mentors and a community of fellow artists and aficionados supporting and rewarding their efforts. It is incredibly rare to find it in someone with no formal training and no network of peers. Yet Vivian Maier is all of these things, a professional nanny, who from the 1950s until the 1990s took over 100,000 photographs worldwide...from France to New York City to Chicago and dozens of other countries...and yet showed the results to no one. The photos are amazing both for the breadth of the work and for the high quality of the humorous, moving, beautiful, and raw images of all facets of city life in America's post-war golden age. It wasn't until local historian John Maloof purchased a box of Maier's negatives from a Chicago auction house and began collecting and championing her marvelous work just a few years ago that any of it saw the light of day. Presented here for the first time in print, 'Vivian Maier: Street Photographer' collects the best of her incredible, unseen body of work."...Publisher description